Ag plasmonic nanostructures and a novel gel electrolyte in a high efficiency TiO2/CdS solar cell1. Issue 15 (21st April 2015) - Kumar, P. Naresh; Deepa, Melepurath; Srivastava, Avanish Kumar
<x xml:space="preserve">Abstract</x> Light scattering and electron accepting characteristics of Ag nanostructures enhance the solar conversion efficiency of a TiO2/CdS film.